Introduction to microfinance - Watkins, Todd A. (World Scientific Pub., 2018)
Microfinance has grown from the obscure efforts of a few philanthropic institutions into a global industry that reaches 150-200 million clients through the branches of thousands of institutions. Microfinance has matured from exclusively funding loans to providing savings, insurance, healthcare, and education. What is microfinance? What are its methods and why? Does it work? What are its prospects and challenges? Why is it controversial? This book tackles these questions and more.